Source term atmospheric release and core inventory analysis for the PUSPATI TRIGA reactor under severe accident conditions - Siti Nur Ain Sulaiman,; Faizal Mohamed,; Ahmad Nabil Ab Rahim,; Mohammad Suhaimi Kassim,; Na’im Shauqi Hamzah, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The estimation of core inventory and source term of nuclear reactor is a part of procedures for conducting a Level 2 Probabilistic Safety Assessment (PSA). Currently, there are not many studies in this area for nuclear research reactors, as it is yet to be made compulsory in the regulatory licensing process among the nuclear-powered countries. This assessment is important to be done in order to be informed about the severity of a nuclear accident. In this study, the type of radionuclides and their activities when unintentionally released to the atmosphere were calculated using the ORIGEN2 code. This work was carried out for PUSPATI TRIGA Reactor (RTP) under a hypothetical severe accident. The core inventory for RTP was determined by assuming the reactor to be operated continuously for 365 days at full power (1 MWt). 42 radionuclides were chosen due to their dominant effects in source term. The atmospheric release of radionuclides is not the same as another depending on the physical condition of the reactor after the accident. The effects of these radionuclides when exposed to the public may cause serious health concern.